Effect of abrasive water jet machining parameters on aramid fibre reinforced plastics composite - Azhari , Mohd Azmir; Khan, Ahsan Ali; Abdullah, Rahmah (Springer, 2009)
Abstract This paper presents a study on the effect of abrasive water jet machining (AWJM) process parameters on surface roughness (Ra) and kerf taper ratio (TR) of aramid fibre reinforced plastics (AFRP) composite. Taguchi’s design of experiment was used as the experimental approach. Through analysis of variance (ANOVA), it was found that the traverse rate was considered to be the most significant factor in both Ra and TR quality criteria. Ra and TR were reduced as increasing the hydraulic pressure and reducing the standoff distance and traverse rate. However, there was no clear pattern for abrasive mass flow rate on both Ra and TR. Therefore, it was confirmed that increasing the kinetic energy of water jet may produce a better quality of cuts. Mathematical models were also developed using multiple linear regression analysis to predict the performance of Ra and TR in terms of AWJM process parameters. Considerably, the models are useful in predicting Ra and TR in AWJM of AFRP laminate as shown in present study.